Effect of geometric configuration of paper micro channels on dilute sample pre-concentration - Teo, Ching Heng Gavin (2018)
Detection concentration of diluted anlaytes is a problem remaining in the fields of diagnosis and monitoring technologies for a longer time. Current techniques used to monitor are more suitable to analytical laboratory purposes and often require pre-concentration of samples using time exhausting methods. These methods include atomic absorption/emission spectroscopy, inductively coupled plasma-mass spectrometry and mass spectrometry. Therefore, scientists focus on microfluidic devices to make sample processing faster and use for point of care diagnosis. The polymer or glass microfluidic devices are difficult to fabricate and time consuming. Thus, this project is proposing to develop a microfluidic paper based analytical device (μPAD) for the pre-concentration by implementing ion concentration polarization as a pre-concentration technique. At first, a convenient and less time consuming fabrication process for the fabrication of μPAD was studied. During the fabrication, the performance for sample concentration by ICP was examined with the use of simple fluorescein sodium solution. Furthermore, the device was optimized to obtain a higher concentration factor by studying the effects of device geometric configuration on sample concentration such as straight and converging channels.